Valoración in vitro de la biodegradación de polietileno de baja densidad mediante hongos filamentosos aislados del relleno sanitario de Pichacay - Cedeño Domínguez, Juan Carlos (2020)
The biodegradation of low-density polyethylene was evaluated through filamentous fungi that were isolated from the Pichacay landfill and fungi belonging to the institutional cepario. The study was done in vitro and weight loss was an indicator of the biodegradable capacity of fungal symptoms, in addition to the FTIR analysis.